Development of a Measure of “Acculturation” for Ethnic Fijians: Methodologic and Conceptual Considerations for Application to Eating Disorders Research - Becker, Anne E. (SAGE Publications, 2010)
Acculturation has been examined as a risk factor for eating disorders, but interpretation of findings has been limited by inconsistent operationalization of this construct across studies. The study aim was to develop and evaluate a population-specific measure of acculturation for ethnic Fijian adolescent schoolgirls, to use in future analyses related to eating disorders. Our findings suggest that acculturation is a multidimensional construct characterized by distinct, though related, dimensions of orientation to ethnic Fijian and/or western/global culture with respect to a range of behaviors and attitudes. In contrast to theoretical models positing uni-dimensional, orthogonal, or oblique relations between cultural identities in individuals undergoing acculturation, our study findings support a heterogeneous pattern among correlations of dimensions across contrasting cultural identities. We suggest multidimensional measures of acculturation are optimal — and socio-demographic proxies inadequate — for characterization of this complex process for health research.